Respuesta :

Mibo

Step-by-step explanation:

x2 - 6x + 8 = 0

x2 - 4x - 2x + 8 = 0

x(x - 4) - 2(x - 4) = 0

(x-4)(x-2) =0

x-4 = 0. x-2 = 0

x = 4. x = 2

Option C is the correct answer

Answer:

C

Step-by-step explanation:

The sum of the roots = - [tex]\frac{b}{a}[/tex]

that is x₁ + x₂ = - [tex]\frac{b}{a}[/tex]

x₁ = 2 and x₂ has to be found

Given

x² - 6x + 8 = 0

with a = 1, b = - 6, c = 8, then

2 + x₂ = - [tex]\frac{-6}{1}[/tex] = 6 ( subtract 2 from both sides )

x₂ = 4

The other solution is x = 4 → C